HUBUNGAN ANTARA KOPING RELIGIUS DENGAN BURNOUT PADA GURU SMK SWASTA X KOTA SEMARANG - Nur Dania Muhandisatin Nadhilah; Ratna Supradewi (Proyeksi: Jurnal Psikologi, 2021)
This study aims to determine the relationship between religious coping and burnout in private vocational school teachers at the X district of Semarang city. The subjects in this study were private vocational school teachers in the X district of Semarang city, totaling 57 peoples. The sampling technique used a saturated sampling technique (census sampling) by taking the entire population. The data were collected using a burnout scale consisting of 35 items with a relibiality coefficient of 0.91 and a religious coping scale consisting of 22 items with a reliability coefficient that moves in the range 0.720-0.890. This study uses correlational quantitative methods and uses product moment statistical data analysis. Based on the results of statistical analysis, it was obtained that the value of rxy = -0.444 with a significance level of p = 0.001 (p≤0.005). The results showed that there was a negative relationship between religious coping and burnout in private vocational school teachers at the X district of Semarang City. The effective contribution of religious coping which affected burnout was 19.7% based on the Rsquare of 0.197, while 80.3% was influenced by other factors.